The contribution of nursing doctoral schools to the development of evidence 10 years after their establishment in Italy: An exploratory descriptive survey of former and current doctoral students' publications. Issue 3 (21st March 2019) - Sasso, Loredana; Watson, Roger; Barisone, Michela; Pellegrini, Ramona; Timmins, Fiona; Aleo, Giuseppe; Bressan, Valentina; Bianchi, Monica; Cadorin, Lucia; Dasso, Nicoletta; Valcarenghi, Dario; Catania, Gianluca; et al.
Abstract: Aim: To analyse through an exploratory descriptive survey how former and current doctoral students' publications have contributed to the development of evidence between the establishment of the doctoral schools of nursing in 2006–2015. Design: An exploratory descriptive survey. Methods: We analysed the papers published in peer‐reviewed journals by the four Italian PhD Schools of Nursing between 2006–2015. Additional missing information was retrieved from Web of Science. Results: We identified 478 scientific papers. The papers increased from 12 in 2006–110 in 2015. Most are published in 29 journals, of which 15 had an impact factor ranging between 0.236–3.755. These results show the increasingly significant contribution of nursing doctoral programmes to the production of evidence, which can be used to improve the quality of nursing and inform health policies. Nursing doctoral schools deserve a greater recognition, especially by Italian funding agencies and political institutions.